2017
DOI: 10.1155/2017/1613657
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome in People Living with Human Immunodeficiency Virus: An Assessment of the Prevalence and the Agreement between Diagnostic Criteria

Abstract: Objectives. We determined metabolic syndrome (MetS) prevalence and assessed the agreement between different diagnostic criteria in HIV-infected South Africans. Method. A random sample included 748 HIV-infected adult patients (79% women) across 17 HIV healthcare facilities in the Western Cape Province. MetS was defined using the Joint Interim Statement (JIS 2009), International Diabetes Federation (IDF 2005), and Adult Treatment Panel III (ATPIII 2005) criteria. Results. Median values were 38 years (age), 5 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
10
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 33 publications
(41 reference statements)
5
10
0
3
Order By: Relevance
“…The JIS result of MS in our finding was higher than the others two. This finding was consistent with the study conducted in Malaysia (26.5, 37.4 and 43.4%) [ 13 ] and South Africa (24.1, 25.5, and 28.2%) respectively [ 14 ]. The prevalence of MS according to JIS in our study was in closer to the finding from South Africa i.e.…”
Section: Discussionsupporting
confidence: 93%
“…The JIS result of MS in our finding was higher than the others two. This finding was consistent with the study conducted in Malaysia (26.5, 37.4 and 43.4%) [ 13 ] and South Africa (24.1, 25.5, and 28.2%) respectively [ 14 ]. The prevalence of MS according to JIS in our study was in closer to the finding from South Africa i.e.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, HIV/AIDS patients with MetS showed statistically higher levels of anthropometric parameters such as BMI, and the waist circumference, as well as systolic and diastolic blood pressure, triglycerides, fasting glucose and HOMA‐IR, and lower levels of HDL, when compared with the group of patients without MetS. Most of these parameters are criteria for MetS and are in accord with the evidence existing in the literature . Furthermore, HIV/AIDS patients with MetS showed higher AST levels, when compared with patients without MetS.…”
Section: Discussionsupporting
confidence: 88%
“…We conducted a cross-sectional study to evaluate whether the serum levels of Cystatin C were correlated with the presence of MetS in HIV/AIDS patients treated with cART. Our study population was similar to the population of HIV patients in Western European countries with MSM and heterosexual patients as predominant groups [25], as well as the prevalence of MetS in HIV/AIDS patients [24,26,27].…”
Section: Discussionmentioning
confidence: 65%
“…The prevalence of MS identified in this study agreed with Wand et al 17 who evaluated the prevalence of MS (8.5% and 7.8% by the IDF and NCEP-ATPIII criteria, respectively) in PLH without the use of ART, but did not agree with the prevalence of Nguyen et al 18 , who reported the prevalence of MS (26.5% and 24.1% by the IDF and NCEP-ATPIII criteria, respectively) in PLH 93% of whom were on ART.…”
Section: Discussionsupporting
confidence: 70%